A Comparative Study between DPC and DPC-SVM Controllers Using dSPACE (DS1104) - Adel Mehdi; Salah-eddine Rezgui; Houssam Medouce; Hocine Benalla (International Journal of Electrical and Computer Engineering (IJECE), 2014)
The aim of this paper is to compare two different control structures. The Simple Direct Power Control (DPC) and the Direct Power Control with Space Vector Modulation (DPC- SVM) for two level converter applications. The ﬁrst strategy (DPC) has been developed to control the instantaneous active and reactive power directly by selecting the optimum switching state of the converter. Applied to the Pulse Width Modulation (PWM) converter its main feature is to improve the total power factor and efﬁciency, even harmonics components existence. In the second structure, the active and reactive powers are used as (PWM) control vari- ables instead of the three-phase line currents usually used in other techniques. It is shown that DPC-SVM exhibits several properties; good dynamic response, constant switching fre- quency, and in particular it provides a sinusoidal line currents. Simulation and experimental results has shown that both control structures achieve good performances.DOI:http://dx.doi.org/10.11591/ijece.v4i3.6074